Examining the Influence of the WEE (Wondering, Exploring, and Explaining) Learning Model on Students' Mathematical Reflective Thinking Proficiency - Lestari, Jepi; Rohman, Ahmad Aunur; Norasia, Yolanda (JURNAL PENDIDIKAN MATEMATIKA, 2023)
The learning process in eighth-grade classes at SMPN 2 Sewon does not adequately support students' development of mathematical reflective thinking abilities. Consequently, students continue to rely heavily on memorization of formulas, leading to persistent challenges in problem-solving. This study aims to investigate the potential impact of the WEE (Wondering, Exploring, and Explaining) learning model on the mathematical reflective thinking abilities of eighth-grade students at SMP N 2 Sewon. This research follows a quantitative approach, employing experimental methods and adopting a posttest-only control design. The study's population consists of eighth-grade students at SMP N 2 Sewon, and a sample of 32 students from class VIII C and 32 students from class VIII D was selected using a cluster random sampling technique. The findings indicate that students who were exposed to the WEE learning model demonstrated superior mathematical reflective thinking abilities compared to those who did not experience this instructional approach. In conclusion, the WEE learning model significantly influences students' mathematical reflective thinking abilities.